Julkinen velka ja tuottavuus-kasvu yksityisten investointien näkökulmasta - Päivi Puonti (The Research Institute of the Finnish Economy (ETLA), 2022)
Corporate investment is crucial for productivity growth. When economic growth is sluggish and productivity growth weak, the government is likely to compensate the shortage of tax revenues with debt. The aim of this research is to study the connection between public indebtedness and productivity growth from the point of view of private investment. According to existing economic research, public debt crowds out private investment slowing down both economic and productivity growth. Our statistical analysis suggests that public debt crowds out private investment and hampers economic growth in Finland, as the share of the corporate sector in the economy decreases with the increase in public indebtedness. Public debt boosts public investment in addition to other expenditure categories, resulting in a leverage effect of private investment in the medium term. This crowding in effect compensates for the negative growth impact of crowding out. The impact occurs at business-cycle frequencies rather than in the long run. This is likely due to the relatively small share of public R&D investment.
Keywords: E22; H63; O40; O47; 330; Public debt; Private investment; Productivity; Crowding out